A single-molecule FRET sensor for monitoring DNA synthesis in real time. Issue 6 (24th January 2017) - Fijen, Carel; Montón Silva, Alejandro; Hochkoeppler, Alejandro; Hohlbein, Johannes
Abstract : We developed a versatile DNA assay and framework for monitoring polymerization of DNA in real time and at the single-molecule level. Abstract : We developed a versatile DNA assay and framework for monitoring polymerization of DNA in real time and at the single-molecule level. The assay consists of an acceptor labelled DNA primer annealed to a DNA template that is labelled on its single stranded, downstream overhang with a donor fluorophore. Upon extension of the primer using a DNA polymerase, the overhang of the template alters its conformation from a random coil to the canonical structure of double stranded DNA. This conformational change increases the distance between the donor and the acceptor fluorophore and can be detected as a decrease in the Förster resonance energy transfer (FRET) efficiency between both fluorophores. Remarkably, the DNA assay does not require any modification of the DNA polymerase and albeit the simple and robust spectroscopic readout facilitates measurements even with conventional fluorimeters or stopped-flow equipment, single-molecule FRET provides additional access to parameters such as the processivity of DNA synthesis and, for one of the three DNA polymerases tested, the detection of binding and dissociation of the DNA polymerase to DNA. We furthermore demonstrate that primer extensions by a single base can be resolved.